Effects of Cropping Year and Artificial Fertilization on Alveographic Quality of GK Öthalom Winter Wheat Variety - Tóth, Árpád; Sipos, Péter; Zoltán, Győri (Acta Agraria Debreceniensis, 2005)
Qualification of winter wheat became more complex for Hungary, after the expansion of the EU. Use of Chopin alveograph is a general method in Western- and Southern Europe. This method is not traditional in Hungary, so determination of alveographic properties of Hungarian winter wheat varieties is very important. Artificial fertilization is one very important component of applied agricultural engineering, which effects winter wheat quality. The another factor is the weather or rather the cropping year, which effects winter wheat quality too. We examined both of them and the alveographic quality of GK Öthalom winter wheat variety between 1996 and 2003.We found that cropping year has significant effect on the alveographic quality of GK Öthalom winter wheat variety on each treatment of artificial fertilization. We found no connection between quantities of precipitations of vegetation periods and the W values of GK Öthalom.We found a strong connection in 1999 and 2003 as well as a very strong connection in 1996, 1997 and 2002, between the increase of fertilizer dose and W values of GK Öthalom. Treatments of artificial fertilization had a significant effect to W values of GK Öthalom in 2001 and 2002. The differences between the two methods are because of large standard deviation of the results.